THE SENSE OF THE ORGANIZATION AND ADMINISTRATION FOR LOURENCO FILHO IN THE CONTEXT OF THE INFLUENCES OF SCIENTIFIC ADMINISTRATION - Mezzari Lopes, Natalina Francisca; Ribeiro, Ricardo [UNESP] (Univ Federal Mato Grosso Sul, 2019)
This article aims to discuss the meaning of organization and administration for Lourenco Filho, in the context of the influences of scientific administration, anchored in the 1920s to 1940s. Based on documentary and bibliographical research, we recover the thought of this educator and administrator of education and of the school, in the Educational Renewal Movement, which marked the History of Brazilian Education. The intention is to understand how such actions have historically helped to produce the concepts of school organization and administration. The theme brings elements of the history of the organization of national education, relating them to the problem of the insertion of scientific administration in the school, which contributes to think the management of education and public school at the present time.
Keywords: School organization; Educational management; School management; School principal